Direct synthesis of imidazolidin-4-ones via cycloadditions of imines with a Leuchs' anyhdride - Sucu, Bilgesu Onur; Ocal, Nuket; Erden, Ihsan (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
A new method for a one-step synthesis of imidazolidin-4-ones has been developed based on tandem nucleophilic additions-decarboxylation-intramolecular cyclizations of imines with a Leuchs' anhydride. Depending on the reaction conditions (with or without base), one either obtains the title compounds, or a-amino acid amide-derived Schiff bases. The latter have also been shown as useful precursors of a-amino acid amides by selective reduction of the imine bond with NaBH4 in the presence of p-T50H. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Leuchs' anhydrides; alpha-Amino acid amides; Imidazolidin-4-ones; Schiff bases; ABSOLUTE-CONFIGURATIONS; NITROGEN ANALOGS; SCHIFF-BASES; ANHYDRIDES; DERIVATIVES; PRIMAQUINE; CONDENSATION; (+/-)-CORYNOLINE; SCOPE; Chemistry